Yeast cell surface display: An efficient strategy for improvement of bioethanol fermentation performance. Issue 2 (4th March 2017) - Chen, Xianzhong
ABSTRACT: The cell surface serves as a functional interface between the inside and the outside of the cell. Within the past 20 y the ability of yeast ( Saccharomyces cerevisiae ) to display heterologous proteins on the cell surface has been demonstrated. Furthermore, S. cerevisiae has been both developed and applied in expression of various proteins on the cell surface. Using this novel and useful strategy, proteins and peptides of various kinds can be displayed on the yeast cell surface by fusing the protein of interest with the glycosylphosphatidylinositol (GPI)-anchoring system. Consolidated bioprocessing (CBP) using S. cerevisiae represents a promising technology for bioethanol production. However, further work is needed to improve the fermentation performance. There is some excellent previous research regarding construction of yeast biocatalyst using the surface display system to decrease cost, increase efficiency of ethanol production and directly utilize starch or biomass for fuel production. In this commentary, we reviewed the yeast surface display system and highlighted recent work. Additionally, the strategy for decrease of phytate phosphate content in dried distillers grains with solubles (DDGS) by display of phytase on the yeast cell surface is discussed.